Teaching Challenges in Limited Face-to-Face Classes in Mathematics Implementation: A Case Study of Modality Transitioning in a High School in the Philippines - Saga, Emmanuel Salazar (SEAMEO Regional Centre for QITEP in Mathematics, 2023)
The modality transitioning introduced by the Department of Education (DepED) gave hope to teachers and students in ensuring quality education amidst pandemic, however, unveiled numerous challenges. The study was concerned in identifying and investigating challenges of the teachers in teaching the students of Bayugan National Comprehensive High School in accordance with its fresh implementation of limited face to face classes. A case study research design was utilized in formulating the research undertaking. Round Table Discussion (RTD) was used by the researcher to gather data relevant to the study. Three (3) Mathematics teachers participated in the RTD. Nineteen (19) virtual participants participated also in the discussion. The conduct of the discussion was held at Bayugan National Comprehensive High School (BNCHS) and was streamed via google meet. Participants’ perspective revealed that pedagogical strategies were not given attention especially majority of the schools in the Philippines offered modular distance learning as a modality. Learners’ performance during distance learning is comparatively low than that of those participating in limited face-to-face classes. While teachers were less equipped with pedagogical strategies for the students under modular distance learning modality, there is a need for determining the challenges encountered in modality transitioning offered in BNCHS.